What makes inpatient treatment for PTSD effective? Investigating daily therapy process factors. (3rd October 2022) - Kratzer, Leonhard; Schiepek, Günter; Heinz, Peter; Schöller, Helmut; Knefel, Matthias; Haselgruber, Alexander; Karatzias, Thanos
Abstract : Objective: Therapeutic process factors including alliance and motivation are considered to play a key role in the treatment of post-traumatic stress disorder (PTSD). Yet, our understanding of change processes in therapy is mostly based on theoretical considerations with limited empirical evidence. In order to identify process characteristics of successful inpatient treatments of PTSD, we investigated the intraindividual, interindividual, and temporal associations of daily assessments of therapy process factors like motivation, alliance, and insight. Method: Therapy process questionnaire (TPQ) assessments were collected from 101 inpatients with PTSD over 50 days, resulting in 5050 assessments. Multilevel vector autoregressive (mlVAR) modelling was applied to investigate the networks of the TPQ factors in a subgroup with good outcome regarding PTSD symptomatology and a subgroup with less favourable outcome. Results: The two subgroups differed markedly in their network models, suggesting that therapy processes might be different for those with good and those with poor treatment outcomes. Conclusions: Our results suggest that good treatment outcome is linked to a specific therapy process dynamic where mindfulness and insight lead to the kind of temporary well-being required to effectively engage with problems and negative emotions, while motivation to change ensures the continuity of confronting negative emotions and problems.